Appendicitis in a baby born to a woman with preeclampsia - Andrea Sarzosa; Jacob Rodríguez; Edy Quizhpe; Carlos Espinosa; Enrique Teran (Elsevier, 2019)
Neonatal appendicitis is a rare and difficult to diagnose condition but with a high mortality. Co-morbidities as necrotizing enterocolitis or Hirschsprung disease are commonly associated, but other conditions as fetal hypoxia or prematurity are considered also as risk factors. Here is reported a case of neonatal appendicitis in a baby from a woman with preeclampsia, suggesting it might also be another prenatal condition to be taken in consideration during the differential diagnosis. : Neonatal appendicitis is a rare condition and this report presents a baby born to teenager women with preeclampsia.